Development and validation of novel AAV2 random libraries displaying peptides of diverse lengths and at diverse capsid positions - Naumer, Matthias; Reuter, Antje; Müller, Oliver J. (Human gene therapy, 2012)
Libraries based on the insertion of random peptide ligands into the capsid of adeno-associated virus type 2 (AAV2) have been widely used to improve the efficiency and selectivity of the AAV vector system. However, so far only libraries of 7-mer peptide ligands have been inserted at one well-characterized capsid position. Here, we expanded the combinatorial AAV2 display system to a panel of novel AAV libraries, displaying peptides of 5, 7, 12, 19, or 26 amino acids in length at capsid position 588 or displaying 7-mer peptides at position 453, the most prominently exposed region of the viral capsid. Library selections on two unrelated cell types—human coronary artery endothelial cells and rat cardiomyoblasts—revealed the isolation of cell type-characteristic peptides of different lengths mediating strongly improved target-cell transduction, except for the 26-mer peptide ligands. Characterization of vector selectivity by transduction of nontarget cells and comparative gene-transduction analysis using a panel of 44 human tumor cell lines revealed that insertion of different-length peptides allows targeting of distinct cellular receptors for cell entry with similar efficiency, but with different selectivity. The application of such novel AAV2 libraries broadens the spectrum of targetable receptors by capsid-modified AAV vectors and provides the opportunity to choose the best suited targeting ligand for a certain application from a number of different candidates.